Effect of Mutated Cu, Zn Superoxide Dismutase (SOD1G93A) on Modulation of Transductional Pathway Mediated by M1 Muscarinic Receptor in SK-N-BE and NSC-34 Cells - Damiano, Simona; Sasso, Anna; Accetta, Roberta; Monda, Marcellino; De Luca, Bruno; Pavone, Luigi Michele; Belfiore, Anna; Santillo, Mariarosaria; Mondola, Paolo (Frontiers in Physiology, 2018)
The constitutive secretion of antioxidant Cu-Zn Superoxide dismutase (SOD1) has been widely demonstrated in many cellular lines. In addition, we showed that as well as the basal SOD1 secretion, this enzyme is also exported through depolarization of excitable cells by high extracellular K concentration. Recent data showed that SOD1 was able to activate muscarinic M1 receptor producing the activation, via phospholipase C, of ERK1-2 and AKT pathways. It is also known that about 20% of familial amyotrophic lateral sclerosis (fALS) is due to mutations in the gene coding for SOD1. The aim of the present research is to evaluate whether, analogously to wild type SOD1 (SOD1wt), the mutated form of SOD1G93A is able to activate ERK1-2 and AKT through muscarinic M1 receptor in SK-N-BE as well as in motoneuron like NSC-34. Our results demonstrated that in NSC-34 and SK-N-BE cells mutated SOD1G93A carried out a more evident activation of ERK1-2 and AKT and a stronger increase of intracellular calcium levels compared to SOD1WT; we also demonstrated that these effects are mediated by the M1 receptor as shown using pyrenzepine, a specific M1 inhibitor and the calcium chelator BAPTA. Of note, M1 receptor pathway activation by SOD1G93A, but not by SOD1WT, is associated with both an increase of reactive oxygen species and a cytotoxic effect.